PENGARUH KOMITE AUDIT, KOMISARIS INDEPENDEN, LEVERAGE, DAN KUALITAS AUDIT TERHADAP INTEGRITAS LAPORAN KEUANGAN PADA BANK UMUM SYARIAH - Anggraeni, Ika Puspita; Zulpahmi, Zulpahmi; Sumardi, Sumardi (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2020)
This study aims to determine the effect of the audit committee, independent commissioners, leverage, and audit quality on the integrity of financial statements in Islamic commercial banks. The method used in this study is the explanatory method, which is to find out or explain the effect of one variable on another variable. The variables studied were variable X, namely audit committee, independent commissioner, leverage, and audit quality, while variable Y was the integrity of financial statements. Data collection techniques are carried out with document review, namely data obtained from the Financial Services Authority (OJK) website and the website of each Islamic commercial bank in the form of financial statements. Data processing and analysis techniques used are descriptive statistics and logistic regression analysis